Effect of Obesity on Developing Diabetes in Adult Population (The Chittagong University Journal of Science, 2023)
Diabetes is a kind of metabolic disease characterized by high blood glucose. High blood glucose occurs because of insufficient secretion of insulin by the pancreas or inability of body's cells to react properly to insulin or both. Problem with eyes, kidney failure, heart attacks, stroke and lower limb amputation are the possible long term effect of diabetes. An important indicator of glycemic control in diabetes is the level of Glycosylated hemoglobin (HbA1c). According to WHO an HbA1c of 6.5% is recommended as the cut point for diagnosing diabetes. This study focuses on the effect of obesity (BMI≥30) of the adults individuals on their HbA1c level based on a longitudinal data. The data for the study were collected from Health and Retirement Study (HRS) sponsored by the National Institute of Aging and conducted by the University of Michigan in USA. It is a nationwide cohort study for Americans over age 50 and their spouses. Profile analysis for longitudinal data is used in the study. Both classical and Bayesian approaches have been applied to carry out the study. The study shows that mean HbA1c is higher in all the time points for the individuals with obesity. Also the steeper trend line of mean HbA1c for individuals with obesity implies that, they are more likely to develop diabetes compared to other.The Chittagong Univ. J. Sci. 44(1): 51-62, 2022